EFFECTIVENESS OF COLD PACK WITH EARLY AMBULATION IN PREVENTING COMPLICATIONS OF HAEMORRHAGE AND HAEMATOMA IN PATIENTS POST CARDIAC CATHETERIZATION - Rizal Ginanjar; Soeharyo Hadisaputro; Mardiyono Mardiyono; Sudirman Sudirman (Belitung Nursing Journal, 2018)
Objective: To examine the effect of early ambulation with cold pack on the prevention of bleeding and haematoma complications in patients post-cardiac catheterization. Methods: This research used an experimental method with randomized posttest-only control group design. Thirty respondents were randomly selected using simple random sampling, with 15 assigned in the experiment and control group. The experiment group was given cold pack and early mobilization, while the control group was given sand pillow with immobilization for 6 hours. Independent t-test and Fisher’s exact test were used for data analysis. Results: Findings showed that there was no significant difference in haemorrhage between experiment and control group after given intervention (p= 1.000), and found a significant difference in haematoma between the two groups (p=0.001). Conclusion: Cold packs with early ambulation and sand pillow with immobilization for 6 hours were equally effective in preventing haemorrhage. However, cold packs with early ambulation was more effective in preventing haematoma.